Acoustofluidics: Acoustofluidic Rotational Manipulation of Cells and Organisms Using Oscillating Solid Structures (Small 37/2016). Issue 37 (4th October 2016) - Ozcelik, Adem; Nama, Nitesh; Huang, Po‐Hsun; Kaynak, Murat; McReynolds, Melanie R.; Hanna‐Rose, Wendy; Huang, Tony Jun
Abstract : On page 5120, T. J. Huang and co‐workers attach a polydimethylsiloxane microchannel featuring sidewall sharp‐edge structures and bare channels, and a piezoelement transducer, to a thin glass slide. Oscillation of polydimethylsiloxane sidewall sharp‐edge structures generates acoustic streaming flows, which in turn rotate single cells and C. elegans inside a microchannel.